PENGEMBANGAN KARAKTER PEDULI LINGKUNGAN ANAK USIA DINI MELALUI BUKU CERITA BERMUATAN SAINS BERWAWASAN KONSERVASI - Yulianti, Dwi; S, Rida N; H, S. S. Dewanti; Diana, Diana (Universitas Negeri Semarang, 2014)
Science is applied in schools including Kindergarten. The results of the interviews with kindergarten teachers in Semarang showed that many teachers have difficulty in teaching science because there is no guide book and companion book about theme-based science materials for the teachers all this time. The method used in this study was Research and Development (RnD). The design was a Quasi Experimental Design in the form of pre-test and One Group Design post-test. The subjects of the study were the teachers and students in group B. The procedure of the study included: (1) Planning, (2) Developing, and (3) Trial. The eligibility and readability were tested using eligibility questionnaires and random tests. The studentsâ character were obtained from the pre-test and posttest questionnaires. The results from the eligibility test showed good criteria. It can be concluded that they are very suitable to be used as a guide book in teaching science (physics) and very suitable to be used as a companion book for the teachers. The readability test results indicated that the teaching materials and the enrichment science (physics) materials show that this enrichment material is easy to understand. The results of the character analysis indicate that the instructional materials in this study is able to develop the studentsâ character.